2022
DOI: 10.1021/acschemneuro.1c00810
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Design of Amyloid-β Species Fluorescent Probes for Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a high mortality and high disability rates neurodegenerative disease characterized by irreversible progression and poses a significant social and economic burden throughout the world. However, currently approved AD therapeutic agents only alleviate symptoms and there is still a lack of practical therapeutic regimens to stop or slow the progression of this disease. Thus, there is urgently needed novel diagnosis tools and drugs for early diagnosis and treatment of AD. Among several AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 90 publications
(153 reference statements)
0
28
0
Order By: Relevance
“…Due to the increased hydrophobicity at the binding site, a hypochromic shift is commonly observed for a variety of Aβ targeting probes and makes their in vivo applications limited. 44 Interestingly, DCM-OH-2-DT not only exhibited fluorescence enhancement, but also showed unchanged maximum emission wavelength at about 730 nm in the presence of Aβ aggregates (Figure 3a). However, DCM-OH-2-MT exhibited two emission peaks, one peak located at 620 nm could be attributed to LE (which was observe with DCM-OH-2) and the other peak at 730 nm (similar to DCM-OH-2-DT) could be originated from the ESIPT emission (Figure 3a).…”
Section: In Vitro Interactions Between the Amphiphilic Dcm-rbfs And A...mentioning
confidence: 97%
“…Due to the increased hydrophobicity at the binding site, a hypochromic shift is commonly observed for a variety of Aβ targeting probes and makes their in vivo applications limited. 44 Interestingly, DCM-OH-2-DT not only exhibited fluorescence enhancement, but also showed unchanged maximum emission wavelength at about 730 nm in the presence of Aβ aggregates (Figure 3a). However, DCM-OH-2-MT exhibited two emission peaks, one peak located at 620 nm could be attributed to LE (which was observe with DCM-OH-2) and the other peak at 730 nm (similar to DCM-OH-2-DT) could be originated from the ESIPT emission (Figure 3a).…”
Section: In Vitro Interactions Between the Amphiphilic Dcm-rbfs And A...mentioning
confidence: 97%
“…Many probes are derived from curcumin, [37][38][39][40][41][42] borodipyrromethane (BODIPY), [43][44][45][46] NIAD dyes, 31,47,48 oxazine dye, 34 and cyanine, 49,50 which have been summarized in the recent reviews as follows. 19,[51][52][53][54] For instance, in 2019, Wong et al reported a review focusing on the design strategies, optical properties, binding capabilities, and the imaging performance of NIRF molecular probes in mice. 52 Liu et al summarized the design strategies of typical NIRF dye probes for monitoring Aβs and Tau species, and highlighted the challenges in developing NIRF dye probes for AD sensing.…”
Section: Danping Zhuangmentioning
confidence: 99%
“…Since the development of AD research has grown rapidly, many reviews have been published on AD diagnosis with a special focus on the strucutre evolutionary of AD probes. 19,[51][52][53]55 In these reviews, less attention has been paid on the several aspects including (i) the mechanisms of binding between the probe and AD biomarkers, (ii) why the NIR probe can cross the BBB, and (iii) the characteristics the probe should possess for efficient BBB crossing. In this section, we fill the gaps and systematically update NIR AD probes reported in the last three years.…”
Section: Different Dyes For Fluorescence Diagnosis Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, curcumin-based near-infrared Aβ fluorescence probes were designed by introducing terminal electron donor and acceptor groups, which showed significant fluorescence enhancement with the presence of Aβ fibrils. In particular, dicyanomethylene has been widely used as the electron acceptor group to construct donor–acceptor architectures with the ability to selectively bind to Aβ aggregates companied with strong fluorescence enhancement [ 16 , 17 ]. Cui and coworkers reported a series of novel near-infrared (NIR) Aβ probes named as DANIR 2a-c which were constructed by the N , N -dimethylaminophenyl-donating group and dicyanomethylene-accepting group bridged by π-conjugated double bonds.…”
Section: Introductionmentioning
confidence: 99%